Japan and “Two China Question” Legacy of World War II - Jintrawet, Pran (Global and Policy Journal of International Relations, 2014)
ABSTRACTThe origin of “Two China Question” is often described as the outcome of Chinese Civil War in1949 between Kuomintang (KMT) and Communist Party of China (CPC). It ideologicallydivided China into two countries which still claimed to be the righteous government of Chinesepeople. It remains salient until now. This paper will discuss the origin of this significantphenomenon by pointing out that the Empire of Japan by that time had importantly involvedin the partition of China. Since 1895, the first Sino-Japanese war, it marked the firstseparation of Chinese-speaking people, Taiwan, from Chinese administration. Taiwanunderwent industrial and agricultural development by Imperial Japan which lately supporteddefeated KMT government to lay its establishment in Taiwan. In the mid of Chinese Civil Warin 1931, Manchuria incident halted the annihilation of CPC by KMT who inevitably had to turntheir attention to Japanese invasion. CPC survived from the abyss of extinction and launchedthe famous long march. In 1937, Marco Polo incident ignited the second Sino-Japanese warand abided KMT to form its alliance with CPC against Imperial Japan. The war consumedKMT’s resources and manpower on the one hand. On the other hand, it provided CPC theprecious time to recover and reconstruct its army. Already in 1945, CPC’s army became moreadvantage than KMT’s on battlefield when Civil War resumed and eventually became thevictor in 1949. This paper suggests that with or without intention the Empire of Japan playedan important role in the emergence of “Two China question”.Keywords: “Two China Question”, Kuomintang (KMT), Communist Party of China (CPC), theEmpire of JapanDOI:https://doi.org/10.33005/jgp.v2i02.2062